Supporting Voices: Groupwork with people suffering from schizophrenia - Randall, Lynda; Walker, Wendy (Groupwork, 2020)
This is an account of a group for schizophrenic people in an acute psychiatric unit attached to a general hospital. Workers in the unit had identified a number of (predominantly) young schizophrenic patients who were thought to be particularly vulnerable to suicide and who needed more help than had hitherto been provided in coming to terms with their illness. These patients possessed a good deal of insight into their condition and their symptoms were well controlled by medication, but they mourmed the loss of previous life-styles and were saddened by their diminishing prospects. The authors describe the setting up of a task-centred, problem-solving group that also sought to develop and maintain communication skills; the choosing of an appropriate therapeutic approach; and the importance of multi-disciplinary communication in a hospital. The group highlighted the feelings of loss and the need to regain control of their lives, experienced by people who are diagnosed as schizophrenic. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.